Endothelial calcium dynamics elicited by ATP release from red blood cells - Ananta Kumar Nayak; Sovan Lal Das; Chaouqi Misbah (Scientific Reports)
Abstract Red blood cells (RBCs) exhibit an interesting response to hydrodynamic flow, releasing adenosine triphosphate (ATP). Subsequently, these liberated ATP molecules initiate a crucial interaction with endothelial cells (ECs), thereby setting off a cascade involving the release of calcium ions (Ca $$^{2+}$$ 2 + ). Ca $$^{2+}$$ 2 + exerts control over a plethora of cellular functions, and acts as a mediator for dilation and contraction of blood vessel walls. This study focuses on the relationship between RBC dynamics and Ca $$^{2+}$$ 2 + dynamics, based on numerical simulations under Poiseuille flow within a linear two-dimensional channel. It is found that the concentration of ATP depends upon a variety of factors, including RBC density, channel width, and the vigor of the flow. The results of our investigation reveals several features. Firstly, the peak amplitude of Ca $$^{2+}$$ 2 + per EC escalates in direct proportion to the augmentation of RBC concentration. Secondly, increasing the flow strength induces a reduction in the time taken to reach the peak of Ca $$^{2+}$$ 2 + concentration, under the condition of a constant channel width. Additionally, when flow strength remains constant, an increase in channel width corresponds to an elevation in calcium peak amplitude, coupled with a decrease in peak time. This implies that Ca $$^{2+}$$ 2 + signals should transition from relatively unconstrained channels to more confined pathways within real vascular networks. This notion gains support from our examination of calcium propagation in a linear channel. In this scenario, the localized Ca $$^{2+}$$ 2 + release initiates a propagating wave that gradually encompasses the entire channel. Notably, our computed propagation speed agrees with observations.